Pendampingan Pemasaran Digital pada Kelompok UKM Kapitan Mandiri dengan framework RACE: Digital Marketing Assistance for the Kapitan Mandiri SME Group Using the RACE Framework - Hanindito, Gregorius Anung; Hasaruddin, Hasaruddin; Pirdianto, Ade Pajar; Subiyantoro, Aditya Ferry; Ibadurrahman, Muhammad; Pranoto, Toni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
West Kotawaringin Regency has substantial potential, especially in tourism. This regency boasts international tourist destinations capable of attracting visitors. Such conditions should ideally drive the development of other industries in West Kotawaringin, including the culinary tourism sector. The culinary tourism industry in West Kotawaringin is largely driven by Small and Medium Enterprises (SMEs). One SME group in this region, Kapitan Mandiri in Sungai Kapitan Village, has promising local fish-based products like amplang (fish crackers), fish chips, fish sticks, and more. However, product marketing has not been optimal due to limited digital literacy among its managers. This community service program aims to provide digital marketing assistance using the RACE (Reach, Act, Convert, Engage) framework to help Kapitan Mandiri design and implement a digital marketing strategy. The program consists of several phases: preparation, implementation, and evaluation. Results show an increase in social media followers, audience engagement, and sales growth of 15-20%. This program is expected to serve as a digitalization assistance model for other SMEs in similar areas.